In vitro Regeneration and Phytochemical Screening of Tylophora indica, an Endangered Medicinal Herb - T. Sellathurai*, S. Rathinavel and (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: In vitro regeneration of Tylophora indica from mature leaf explants placed on MS with low concentration (1mM) of Kin and BA alone and in combination with Kin and BA induced multiple shoots and roots. Leaf explants on MS with BA and 2, 4-D or NAA along with Ads had poor organogenic responses. The responses of leaf explants in MS + Kin (1mM) implicate the feasibility for multiplication of this species. Comparative phytochemical analysis revealed the presence of alkaloids, steroids and carbohydrates both in adult leaf and in vitro derived callus. It evidences the potential utility of tissue cultures for production of bioactive compounds. It may be concluded that further standardization of hormonal combinations could helpful for large scale propagation and extraction of drugs for pharmaceutical application.